2021
DOI: 10.1097/mcp.0000000000000822
|View full text |Cite
|
Sign up to set email alerts
|

Sleep medicine and coronavirus disease 2019

Abstract: Purpose of reviewTo evaluate the impact of the COVID-19 pandemic on the care of people with sleep disorders, to explore relationships between OSA and COVID-19, and to describe current knowledge of the effect of the pandemic on sleep globally.Recent findingsCOVID-19 has led to significant changes in the practice of sleep medicine, including the care of patients with OSA. An OSA diagnosis may portend a worse prognosis with COVID-19, whilst prior COVID-19 may have an impact on sleep breathing.SummaryThe pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The disparities in sleep disturbance proportions and changes across countries may be explained, at least in part, by differences in pandemic control policy and general perception of the COVID-19 crisis. [ 16 , 17 ] Interestingly, Kocevska et al, reported that 20 of pre-pandemic deep sleep had exacerbated sleep issues during postCOVID-19 era, while a 25% of respondents with pre-pandemic low quality sleep had improved sleep during the COVID-19 pandemic. [ 35 ] They contended that the impacts of COVID-19 on sleep quality are not uniform, emphasizing individual differences in response to the COVID-19 crisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disparities in sleep disturbance proportions and changes across countries may be explained, at least in part, by differences in pandemic control policy and general perception of the COVID-19 crisis. [ 16 , 17 ] Interestingly, Kocevska et al, reported that 20 of pre-pandemic deep sleep had exacerbated sleep issues during postCOVID-19 era, while a 25% of respondents with pre-pandemic low quality sleep had improved sleep during the COVID-19 pandemic. [ 35 ] They contended that the impacts of COVID-19 on sleep quality are not uniform, emphasizing individual differences in response to the COVID-19 crisis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 14 ] Despite reports revealing poor in hospitalized patients, sleep quality is important, and sleeping issues in recovered COVID-19 people require more research. [ 15 , 16 ] Sleep disorders may exacerbate the consequences of COVID-19 on physical and mental health. [ 17 ] Compared to COVID-19 patients who did not have sleep disturbances, patients with sleep disturbances reported a greater rate of hospital-acquired infections, broader hospital stays, and a more significant requirement for ICU entrance.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of sleep disturbance increased from 54% to 66% in OSA patients and from 29% to 40% in the control group during the COVID-19 pandemic, as reported by Spicuzza et al However, there was no significant difference in the percentage of depression between OSA patients and controls (61% vs. 65%) [ 15 ]. A review by Gill et al found that adherence to CPAP therapy may have improved, and the use of remote consultations and telemonitoring increased during the COVID-19 pandemic [ 16 ]. A study by Demirovic et al demonstrated that CPAP adherence improved during the COVID-19 lockdown in severe OSA patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…An early detection algorithm (EDA) that includes sleep parameters should be developed. Wearable devices could be useful in limiting the transmission of infection during a critical period in the disease process by alerting users of a possible early infection [ 10 , 11 ]. Additionally, this case study shows how data from devices they routinely wear could be used for medical purposes constituting a potential paradigm shift in clinical practice.…”
Section: Discussionmentioning
confidence: 99%